Economic literacy: An international comparison - Tullio Jappelli (Goethe University Frankfurt, Center for Financial Studies (CFS), 2010)
Many studies show that most people are not financially literate and are unfamiliar with even the most basic economic concepts. However, the evidence on the determinants of economic literacy is scant. This paper uses international panel data on 55 countries from 1995 to 2008, merging indicators of economic literacy with a large set of macroeconomic and institutional variables. Results show that there is substantial heterogeneity of financial and economic competence across countries, and that human capital indicators (PISA test scores and college attendance) are positively correlated with economic literacy. Furthermore, inhabitants of countries with more generous social security systems are generally less literate, lending support to the hypothesis that the incentives to acquire economic literacy are related to the amount of resources available for private accumulation.
urn:nbn:de:hebis:30-78683
Keywords: E2; D8; G1; 330; Economic Literacy; Human Capital; Social Security